Influence of annealing on the bias voltage dependence of tunnelling magnetoresistance in MgO double-barrier magnetic tunnel junctions with CoFeB electrodes - FENG, GEN; VAN DIJKEN, SEBASTIAN; COEY, JOHN MICHAEL DAVID (American Institute of Physics, 2006)
Double-barrier magnetic tunnel junctions with two MgO barriers and three CoFeB layers exhibiting tunneling magnetoresistance (TMR) values of more than 100% were fabricated. The bias voltage dependence of the TMR ratio is highly asymmetric after annealing at low temperatures, indicating dissimilar CoFeB/MgO interfaces. The TMR effect decays very slowly for positive bias and is only reduced to half of its maximum value at V1/2 = 1.88?V when the junctions are processed at 200??C. The largest output voltage, 0.62?V, is obtained after annealing at 300??C, a temperature that combines high TMR ratios with a considerable asymmetric bias dependence.
PUBLISHED
Keywords: Physics